2017
DOI: 10.1016/j.jmbbm.2016.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental investigation into mechanical performances of Poly-L-Lactide Acid (PLLA) coronary stents

Abstract: Poly-L-lactide Acid (PLLA), as a credible biodegradable polymer-based material, can provide a promising amount of degradation time for vessel remodeling. Served as a sort of reliable intravascular implants, PLLA stents are expected to provide sufficient scaffolding to the target arteries without generating too much recoil after deployment. Besides, the stress and strain distribution should be as homogeneous as possible, and the stent conformability in fitting to the nature curvature of the vessels needs to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 25 publications
5
55
0
7
Order By: Relevance
“…Our results have shown that the elastic recoil for crimping was 13.9% and the one for expansion was 4.53%. This aligns with the observations by Wang et al [5], who reported a radial recoil for PLLA stent crimping and expansion as 10.87% and 4.19%, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results have shown that the elastic recoil for crimping was 13.9% and the one for expansion was 4.53%. This aligns with the observations by Wang et al [5], who reported a radial recoil for PLLA stent crimping and expansion as 10.87% and 4.19%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This will, in turn, induce larger stress and strain in the arterial walls, leading to a greater risk of mechanical injury and tissue inflammation [5]. Our results have shown that the elastic recoil for crimping was 13.9% and the one for expansion was 4.53%.…”
Section: Discussionmentioning
confidence: 79%
“…in air or in a submerged environment, to feed higher-level analyses of device performance, e.g. crimping, inflation, and load bearing capability [13,23]. However, viscoelastic-plastic polymers, such as pLLA, consist of heterogeneous microstructural compartments including crystal domains, where molecules are differentially aligned and packed, and amorphous regions where they are randomly oriented.…”
Section: Discussionmentioning
confidence: 99%
“…Inflation rate affected stent expansion mainly during inflation process, while not much difference was shown after balloon deflation. Wang et al [36] studied the mechanical deformation of a PLLA biodegradable coronary stent using experimental and computational methods. They modelled the crimping of stent to an outer diameter of 1.41 mm and subsequent expansion to different inner diameters.…”
Section: Stent Deploymentmentioning
confidence: 99%